Consolidating sustainability efforts: The role of effective supply chain management in balancing economic growth, environmental stewardship, and social responsibility - Abubkr Abdelraheem; Asaad Musa; Mohamed Khogly; Yosra Elboukhari (Journal of Project Management)
This study explores the relationship between supply chain practices and sustainability efforts, with the understanding that logistics strategies can have profound impacts on economic growth, society, and environmental conservation. The primary objective of the research is to identify ways in which organizations can improve their supply chains to achieve more favorable sustainability outcomes by examining the relationship between the supply chain and sustainability performance. Data was collected through a questionnaire designed and distributed to 43 companies in the basic materials sector in the Kingdom of Saudi Arabia. The questionnaire data were analyzed using SPSS and Smartpls. The results indicate that supply chains in the basic materials sector in the Kingdom are operating effectively and positively, impacting the promotion of economic, social, and environmental sustainability. The insights from this study can help advance the understanding of how supply chains can drive sustainability improvements while developing a more robust economic framework for sustainability and resource management for stakeholders.